Incidental finding of regressed solitary unilateral choroidal metastasis from lung adenocarcinoma with EGFR exon-19 deletion treated with erlotinib. Issue 1 (18th January 2021) - Padhy, Srikanta Kumar; Kaliki, Swathi
Abstract : A 49-year-old Asian Indian woman, with a previous history of biopsy proven stage IV primary lung adenocarcinoma with metastasis to liver, bones and central nervous system, presented with 1-month history of photopsia in right eye. She was on oral erlotinib since 6 months. Dilated fundus examination of right eye revealed a solitary dome-shaped brownish elevated lesion of approximately 1-disc diameter along the inferotemporal midperiphery with surrounding areas of hypopigmentation. Based on multimodal imaging, a diagnosis of resolved solitary unilateral choroidal metastasis from lung carcinoma in the right eye was made. In view of inactive and regressed choroidal metastasis, no intervention was mandated.